Kebutuhan Keluarga Pasien yang Dirawat di Intensive Care Unit (ICU): Literature Review - Alfi Rusdianti; Fitri Arofiati (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2019)
Intensive care unit (ICU) is in principle not designed to accept the presence of a patient's visitor or family for a long time. One of the effects that arises is an increase in the patient's family anxiety. In general, nurses do not consider the patient's family as part of his holistic care. So, it takes the role of nurses to identify the patient's family needs, in order to realize holistic care. This review aims to identify the family needs of patients treated in the intensive care unit. Literature is obtained from the Ebsco database, ProQuest and Science Direct, using keywords: family needs, nursing strategy and intensive care unit. From 7 literature sources obtained about what is needed by the patient's family. This review produced 5 themes, namely family needs for information, closeness, support, involvement, and knowing the care received by patients. This review only focuses on the patient's family needs in general. The family is part of the patient. Identified family needs, namely information needs, closeness, support, involvement and knowledge of care received by patients. The participation of health workers is needed in identifying and encouraging the fulfillment of family needs. Keyword: family needs, nursing strategies, intensive care unit